Refinement of the Reflective Function Questionnaire for Youth (RFQY) Scale B Using Item Response Theory. (September 2022) - Sharp, Carla; Steinberg, Lynne; McLaren, Veronica; Weir, Stuart; Ha, Carolyn; Fonagy, Peter
We conducted item response theory analyses to refine the Reflective Function Questionnaire for Youth (RFQY) Scale B. Data from a non-clinical sample of young people ( n = 737; aged 18-25 years) was used to derive a shortened version of the RFQY. Results were replicated in a clinical sample of inpatient adolescents ( n = 467; aged 12-17 year), resulting in a five-item measure, thereafter named the RFQY-5. The RFQY-5 item set was then scrutinized for construct validity against the original 23-item RFQY item set in a randomly selected sample of 100 inpatient adolescents not included in the item response theory replication, and 186 healthy adolescents drawn from the community. Results showed that the RFQY-5 performed similarly as the long version in terms of associations with criterion variables, and outperformed the longer version in discriminating between inpatient and community-dwelling adolescents who differed in their levels of borderline traits. The study provides evidence in support of the use of the RFQY-5 in research and clinical settings.